The beneficial effect of sulforaphane on platelet responsiveness during caloric load: a single-intake, double-blind, placebo-controlled, crossover trial in healthy participants - van Steenwijk, Hidde P.; Winter, Evi; Knaven, Edward; Brouwers, Jos F.; van Baardwijk, Myrthe; van Dalum, Jasper B.; Luijendijk, Teus J. C.; van Osch, Frits H. M.; Troost, Freddy J.; Bast, Aalt; Semen, Khrystyna O.; de Boer, Alie (Frontiers in Nutrition, 2023)
Background & Aims: As our understanding of platelet activation in response to infections and/or inflammatory conditions is growing, it is becoming clearer that safe, yet efficacious, platelet-targeted phytochemicals could improve public health beyond the field of cardiovascular diseases. The phytonutrient sulforaphane shows promise for clinical use due to its effect on inflammatory pathways, favorable pharmacokinetic profile, and high bioavailability. The ability of sulforaphane to improve platelet functionality in impaired metabolic processes has however hardly been studied in humans. This study investigated the effects of broccoli sprout consumption, as a source of sulforaphane, on urinary 11-dehydro-thromboxane B2 (TXB2), a stable thromboxane metabolite used to monitor eicosanoid biosynthesis and response to antithrombotic therapy, in healthy participants exposed to caloric overload. Methods: In this double-blind, placebo-controlled, crossover trial twelve healthy participants were administered 25 mg of sulforaphane, or placebo followed by the standardized high-caloric drink PhenFlex given to disturb healthy homeostasis. Urine samples were collected during the study visits and analyzed for 11-dehydro-TXB2, sulforaphane and its metabolites. Genotyping was performed using Illumina GSA v3.0 DTCBooster. Results: Administration of broccoli sprouts before the caloric load reduced urinary 11-dehydro-TXB2 levels by 50% (p = 0.018). The amount of sulforaphane excreted in the urine during the study visits correlated negatively with 11-dehydro-TXB2 (rs = -0.377, p = 0.025). Participants carrying the polymorphic variant NAD(P)H dehydrogenase quinone 1 (NQO1*2) showed decreased excretion of sulforaphane during the study visits (p = 0.035). Conclusions: Sulforaphane was shown to be effective in targeting platelet responsiveness after a single intake. Our results indicate an inverse causal relationship between sulforaphane and 11-dehydro-TXB2, which is unaffected by the concomitant intake of the metabolic challenge. 11-dehydro-TXB2 shows promise as a non-invasive, sensitive, and suitable biomarker to investigate the effects of phytonutrients on platelet aggregation within hours. Trial registration number: NCT05146804 at www.clinicaltrials.gov.